Genetic conversion of a split-drive into a full-drive element - Gerard Terradas; Jared B. Bennett; Zhiqian Li; John M. Marshall; Ethan Bier (Nature Communications, 2023)
CRISPR-based gene-drives can carry the Cas9 and guide RNA (gRNA) components in a single-linked cassette or in separate elements inserted into different genomic loci. Here the authors genetically transform and compare full versus split drives, with the former performing less efficiently than predicted.